Jenis-Jenis Burung Yang Diperjual-Belikan Di Pasar Burung Palembang Sumatera Selatan - Dian Mutiara; Syamsul Rizal; Muhammad Royan (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Research on the types of orders of Passeriformes that have been traded at the Palembang bird market in South Sumatra has been carried out. The aim of this study was to find out the types of Passeriformes sequences, including endemic birds, protected birds and endangered Sumatran birds that were traded at the Palembang bird market. South Sumatra. This research was conducted in January-April 2019, at the bird market on the old Masjid Jalan, Kelurahan 17 Ilir and Pasar Cinde on Jalan Jendral Sudirman. The method used is purposive sampling. Bird identification was carried out at the Biology Laboratory, Faculty of Mathematics and Natural Sciences, University of PGRI Palembang. The types of Order Passers found were 12 Familia, 23 Genus, and 31 Species. Familia Sturnidae which has the highest diversity of species, namely 5 species.